Foreign Physicians: Discriminatory Patient Preferences and Doctor Availability - Brigham Walker; Janna Wisniewski; Sarah Tinkler; Miron Stano; Rajiv Sharma (Institute of Labor Economics (IZA), 2023)
Roughly a quarter of physicians in the United States are either international medical graduates (IMGs) or foreign-born physicians (FBPs). We propose a theoretical model where patient preferences that disfavor IMGs and FBPs may result in those physicians offering better access to their services compared with non-IMGs/FBPs in equilibrium. We use data from two field experiments to test the predictions from the model: one concerning patient preferences and the other concerning physician availability. In the patient preferences field experiment, we find that patients strongly prefer doctors educated in the United States to IMGs by about 2-to-1. In the physician availability field experiment, we find that US-born physicians generally have lower levels of availability including offering fewer appointments and longer wait times. These results indicate a substantial underutilization of FBPs relative to US-born physicians and suggest that a sizable share of the US healthcare provider base is unfairly disadvantaged based on nativity.
Keywords: I11; C93; J7; 330; patient preferences; physician availability; foreign doctors; International Medical Graduates (IMGs); Foreign-Born Physicians (FBPs)